Surgical management of gingival recession: A clinical update - Hamdan Alghamdi; Nadir Babay; Anil Sukumaran (Elsevier, 2009)
Gingival recession is defined as the apical migration of the junctional epithelium with exposure of root surfaces. It is a common condition seen in both dentally aware populations and those with limited access to dental care. The etiology of the condition is multifactorial but is commonly associated with underlying alveolar morphology, tooth brushing, mechanical trauma and periodontal disease. Given the high rate of gingival recession defects among the general population, it is imperative that dental practitioners have an understanding of the etiology, complications and the management of the condition. The following review describes the surgical techniques to treat gingival recession.